Bibliographic trends in mineral fiber-reinforced concrete: A scientometric analysis - Mohamad Moasas, Abdulrhman; Amin, Muhammad Nasir; Ahmad, Waqas; Khan, Kaffayatullah; Al-Hashem, Mohammed Najeeb; Qureshi, Hisham Jahangir; Mohamed, Abdullah (Frontiers in Materials, 2022)
In the construction industry, pursuing sustainable development by using sustainable materials necessitates using renewable resources. Among different renewable materials, mineral-derived natural fibers are relatively cheaper and abundantly available in various countries. This study summarizes the research advancements on concrete reinforced with mineral-derived natural fibers. This review on the incorporation of mineral fibers in concrete evaluates, identifies, and synthesizes research outcomes for creating a summary of current evidence which can contribute to evidence-based practice. Mapping knowledge, c/o-occurrence, and co-citation are hard gears for innovative research. Accordingly, the present study is aimed at exploring the literature on key features of mineral fiber-reinforced concrete by performing a scientometric analysis. The current study implemented an advanced approach for mining, processing, and analyzing data, interpretation, and presentation of available bibliographic data on mineral fibers in concrete. Furthermore, the discussion on the applications and limitations of using mineral fiber-reinforced concrete in the construction industry is also made. The current research may aid academics in exchanging new ideas and techniques and developing collective efforts.